Analysis of the objective internal load in Portuguese skydivers in the first jump of the day - MACHADO, Tiago (2022)
The general objective of this study was to identify the variation in heart rate (HR) of Portuguese skydivers during 6 moments in their first jump of the day, bearing in mind the variable level of experience. Thirty-one Portuguese skydivers, 28 men and 3 women, aged between 19 and 62, participated in the study, 12 had A and B licenses (less experienced) and 19 had C and D licences (more experienced). The instrument used to record the heart rate of the skydivers at the different moments of their first jump of the day was the WIMU PRO. A repeated measures analysis of variance was used to analyse HR at different moments in the jump and its relation with the variables level of experience. Bonferroni multiple comparisons were performed to study the importance of the differences observed in HR at the different moments. The effect size was evaluated with partial eta squared. The results showed that average HR in this group of skydivers was 130 bpm, in the different moments of the jump. HR increases from the value recorded at rest until the moment of jumping from the plane and opening the parachute, reaching the highest average at that moment, then decreasing until contact with the ground. Comparing the variable, we found that the less experienced had higher HR than the more experienced at all moments during the jump. Statistically significant differences were found at the different moments of the jump, regarding HR (Max: p < 0.001, η 2 p = 0.820; Min: p < 0.001, η 2 p = 0.821; AVG: p < 0.001, η 2 p = 0.834) Level of experience with jumping moment interaction, we only verified differences related to HR Min (p = 0.007, η 2 p = 0.056),. With regard to experience, the identified differences were not statistically significant. Skydiving triggers an acute adaptive cardiovascular response which is reflected in the increase in the HR, between the moment of boarding the plane and the moment at which the parachute opens, thereafter decreasing until contact with the ground. The most experienced parachutists recorded the highest HR at the moment of landing and the least experienced at the moment of free fall.